Nutritional management for a patient with dysphagia and respiratory failure after stroke (1例脑卒中后吞咽障碍合并呼吸衰竭患者的营养管理) - HE Juan (贺娟); WANG Chunyan (王春艳); LI Xiaoxia (李小霞) (中西医结合护理)
This article summarized the nutrition management of a patient with dysphagia and respiratory failure after stroke. Without affecting the internal environment, dynamic personalized enteral and parenteral nutrition were carried out to meet the body’s caloric and nitrogen needs, improve the nutritional status, and reduce the incidence of complications. (本文总结1例脑卒中后吞咽障碍合并呼吸衰竭患者的营养管理体会。通过施行动态、个性化的肠内、肠外营养的支持, 在不影响机体内环境的情况下, 可满足机体对热量和氮的需要, 并可改善重症患者的营养状况, 减少并发症的发生。)